Xylaria necrophora, sp. nov., is an emerging root-associated pathogen responsible for taproot decline of soybean in the southern United States. (4th March 2021) - Garcia-Aroca, Teddy; Price, Paul P.; Tomaso-Peterson, Maria; Allen, Tom W.; Wilkerson, Tessie H.; Spurlock, Terry N.; Faske, Travis R.; Bluhm, Burt; Conner, Kassie; Sikora, Edward; Guyer, Rachel; Kelly, Heather; et al.
ABSTRACT: Taproot decline (TRD) is a disease of soybean that has been reported recently from the southern United States (U.S.). Symptoms of TRD include foliar interveinal chlorosis followed by necrosis. Darkened, charcoal-colored areas of thin stromatic tissue are evident on the taproot and lateral roots along with areas of necrosis within the root and white mycelia within the pith. Upright stromata typical of Xylaria can be observed on crop debris and emerging from infested roots in fields where taproot decline is present, but these have not been determined to contain fertile perithecia. Symptomatic plant material was collected across the known range of the disease in the southern U.S., and the causal agent was isolated from roots. Four loci, ⍺-actin ( ACT ), β-tubulin ( TUB2 ), the nuclear rDNA internal transcribed spacers (nrITS), and the RNA polymerase subunit II ( RPB2 ), were sequenced from representative isolates. Both maximum likelihood and Bayesian phylogenetic analyses showed consistent clustering of representative TRD isolates in a highly supported clade within the Xylaria arbuscula species complex in the "HY" clade of the family Xylariaceae, distinct from any previously described taxa. In order to understand the origin of this pathogen, we sequenced herbarium specimens previously determined to be " Xylaria arbuscula " based on morphology and xylariaceous endophytes collected in the southern U.S. Some historical specimens from U.S. herbaria collected in the southern region as saprophytes as well as a single specimen from Martinique clustered within the "TRD" clade in phylogenetic analyses, suggesting a possible shift in lifestyle. The remaining specimens that clustered within the family Xylariaceae, but outside of the "TRD" clade, are reported. Both morphological evidence and molecular evidence indicate that the TRD pathogen is a novel species, which is described as Xylaria necrophora .